The Contribution of Learning Resources and Parent's Attention to Learning Outcomes - Ananda, Oki Surya; Maksum, Hasan (Journal of Education Reseach and Evaluation, 2021)
Low student learning outcomes in digital communication simulation subjects, so that learning resources and parents' attention are needed to be more enthusiastic and active in learning. This study aims to analyze the contribution of mastery of learning resources and parents' attention to learning outcomes. This type of research is descriptive correlational. The study population was 340 students. This study's sample was 72 students with a sampling technique of 25% of the total population. The data collection method used is by giving a questionnaire. The instrument used was a questionnaire in the form of a Likert scale. The data analysis technique used is simple regression and multiple regression. The results showed that learning resources and parents' attention contributed together to learning outcomes by 43.6%. Based on the research results, it can be concluded that the learning resources and parents' attention simultaneously contribute to learning outcomes. This research implies that learning resources and parents' attention can motivate students to be more enthusiastic and active in learning.